Drug utilization patterns of flupirtine following implementation of risk minimization measures in Germany. (3rd August 2019) - Kaplan, Sigal; Ehlken, Birgit; Hamann, Xenia
Abstract: Objectives: This report characterizes flupirtine prescribing patterns before and after the implementation of risk minimization measures (RMM) in Germany as a complementary analysis to support previous study findings. Methods: A retrospective analysis was conducted using a patient-level longitudinal prescription database (IMS LRx) in Germany. The study population included patients who were prescribed flupirtine-containing products. One-year periods before (2012) and after (April 2015–March 2016) RMM implementation were assessed for the following measures: flupirtine use of up to two weeks, flupirtine use when other analgesics are contraindicated and concomitant use of drugs with a known potential to induce liver injury. Results: The number of flupirtine users decreased by 41.0% from 248, 738 patients in the pre-RMM implementation period to 146, 764 in the post-implementation period. The proportion of patients prescribed flupirtine for up to 14 days increased significantly by 22.7%, from 67.9% to 90.6% in the pre- to post-implementation periods, respectively. Over half the patients received long-term medications for conditions contraindicated with the use of other analgesics within 12 months prior to the first flupirtine prescription in the pre- and post-implementation periods (57.1% and 52.3%, respectively). Concomitant prescriptions of drugs with known potential hepatotoxic effects were recorded in 36.6% and 34.2% of flupirtine prescriptions during the pre- and post-implementation periods, respectively. Conclusions: While physicians generally restricted flupirtine prescriptions to the short-term treatment duration recommended in the labeling, the other labeling recommendations were not as stringently adopted. Findings of this investigation support a previous study conducted in an electronic medical record database.